Precancerous Lesions of the Oral Mucosa - (:unkn) unknown (DERI ZUHREVI HASTALIKLAR DERNEGI, 2012)
In this review of oral precancerous lesions, leukoplakia, elythroleukoplakia/erythroplakia and the least common variant proliferative verrucous leukoplakia will be focused with their clinical characteristics and their potential to develop oral squamous cell carcinoma and related factors will be discussed. (Turkderm 2012; 46 Suppl 2: 86-9)
Keywords: Leukoplakia; erythroplakia; proliferative verrucous leukoplakia; pre-cancer; PROLIFERATIVE VERRUCOUS LEUKOPLAKIA